2004
DOI: 10.1177/0015732515040112
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Foreign-Market Environments for International Franchising Expansion

Abstract: The purpose of this study is to investigate the influence of environmental factors on international franchising, and to offer a normative model to evaluate the international franchising environment. Using correlation analysis, this study finds that environmental factors including economic, demographic, cultural and political factors are related to and may influence the decision of franchisers to expand their operations in a host country. The study suggests that franchising practitioners conduct an environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 4 publications
1
10
0
2
Order By: Relevance
“…Entrepreneurial cultures are often associated with high levels of individualism and masculinity. As such, Alon, Toncar, and McKee (2000) suggested that particularly high levels in masculinity and individualism are preferable franchising country-related factors. A direct test of Hofstede's scale reveals a positive correlation between the dual factors of individualism and masculinity on the total level of international franchising (Toncar, Alon, & McKee, 2000).…”
Section: The Social Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Entrepreneurial cultures are often associated with high levels of individualism and masculinity. As such, Alon, Toncar, and McKee (2000) suggested that particularly high levels in masculinity and individualism are preferable franchising country-related factors. A direct test of Hofstede's scale reveals a positive correlation between the dual factors of individualism and masculinity on the total level of international franchising (Toncar, Alon, & McKee, 2000).…”
Section: The Social Environmentmentioning
confidence: 99%
“…As such, Alon, Toncar, and McKee (2000) suggested that particularly high levels in masculinity and individualism are preferable franchising country-related factors. A direct test of Hofstede's scale reveals a positive correlation between the dual factors of individualism and masculinity on the total level of international franchising (Toncar, Alon, & McKee, 2000). Russia, for example, with a relatively high level of collectivism and low level of masculinity, is culturally unattractive to franchising as compared to the United States (Anttonen, Tuunanen, & Alon, 2005).…”
Section: The Social Environmentmentioning
confidence: 99%
“…International franchising is fast becoming the focus of investigation (Alon et al, 2000;Welsh and Alon, 2001). Franchising is one of the fastest growing US exports (Paswan et al, 2001a;Zeidman, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Os aspectos referentes aos fatores socioculturais são determinantes para a compreensão dos valores e normas culturais locais, afetando a aceitação por marcas estrangeiras e determinando padrões de negociação, não obstante ser um indicador capaz de sinalizar a estrutura social de um país no que diz respeito ao nível de educação formal, saúde e renda (ALIOUCHE & SCHLENTRICH, 2011;ALON & SHOHAM, 2010;ALIOUCHE & SCHLENTRICH, 2009;CUERVO-CAZURRA, 2008;ALON & MCKEE, 1999;ALON et al, 2000).…”
Section: Organizacionais Existentes Entre As Redes De Franquias Brasiunclassified
“…• Fatores socioculturais: caracterizar a estrutura sociocultural dos países de destino mediante os seguintes indicadores: (i) índice de desenvolvimento humano e (ii) padrões culturais e sociais em comum (ALIOUCHE & SCHLENTRICH, 2009;ALIOUCHE & SCHLENTRICH, 2011;ALON & SHOHAM, 2010;ALON & MCKEE, 1999a;ALON et al, 2000).…”
Section: Redes De Franquias Brasileiras Com Operações Internacionaisunclassified